PERAN DPRD DALAM FUNGSINYA SEBAGAI PENGAWASAN TERHADAP PENGGUNAAN KEUANGAN DAERAH OLEH EKSEKUTIF - Wisnu Wahyudha, Tjokorda Gde; Artadi, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015, 2015)
Since the issuance of regulations regarding to regional autonomy Act No. 23 year of 2014 on Regional Government and Law No. 33 year of 2004 on Financial Balance between Central and Local Government, so the powers and responsibilities assigned to local governments to manage the region optimally be grater. It required a huge role of the legislators to control the financial related policy areas which is economical, efficient, effective, transparent, and accountable and factors that affect the value of the government’s financial reporting information. The method used in writting this paper is normative research. In terms of the role, the representative council shall supervise the implementation of the budget (APBD) as a form of governance and accountability of the organization of services oriented to the public interest. Factors that affect the value of the government’s financial reporting information, among others are, the quality of human resource, the use of technology, system of internal supervise and monitoring.
Keywords: Role, Supervision, Parliament